Medical student selection interviews: insights into non-verbal observable communications: a cross-sectional study - Pin-Hsiang Huang; Kang-Chen Fan; Alexander Waits; Boaz Shulruf; Yi-Fang Chuang (Korean Journal of Medical Education)
Purpose Interviews play a crucial role in the medical school selection process, although little is known about interviewers’ non-verbal observable communications (NoVOC) during the interviews. This study investigates how interviewers perceive NoVOC exhibited by interviewees in two medical schools, one in Taiwan and the other in Australia. The study also explores potential cross-cultural differences in these perceptions. Methods A 26-item questionnaire was developed using a Delphi-like method to identify NoVOC. Interviewers from the University of New South Wales, Australia, and National Yang Ming Chiao Tung University, Taiwan (n=47 and N=78, respectively) rated these NoVOC between 2018 and 2021. Factor analyses identified and validated underlying factors. Measurement invariance across countries and genders was examined. Results A total of 125 interviewers completed the questionnaire, including 78 from Taiwan and 47 from Australia. Using exploratory factor analysis, 14 items yielded reliable three factors “charming,” “disengaged,” and “anxious” (Cronbach’s α=0.853, 0.714, and 0.628, respectively). The measurement invariance analysis indicated that the factor models were invariant across genders but significantly different between the two countries. Further analysis revealed inconsistencies in interpreting the “anxious” factor between Taiwan and Australia. Conclusion The three distinct factors revealed in this study provide valuable insights into the NoVOC that interviewers perceive and evaluate during the interview process. The findings highlight the importance of considering non-verbal communication in selecting medical students and emphasize the need for training and awareness among interviewers. Understanding the impact of non-verbal behaviors can improve selection processes to mitigate bias and enhance the fairness and reliability of medical student selection.